Strategic Management - Rothaermel, Frank T. (McGraw Hill, 2024)
Frank T. Rothaermel wrote Strategic Management 6e from the ground up because the world has changed dramatically since 5e was published (in January 2020). Events such as the COVID-19 pandemic, social justice movements, war, and disenchantment with the economic system profoundly impact how leaders run companies in their quest for competitive advantage. Rothaermel 6e synthesizes and integrates conceptual frameworks, empirical research, and practical applications with current real-world examples to help students make sense of a fast-changing and complex world. Rothaermel 6e is industry-leading in diversity and inclusion by featuring leaders with different backgrounds and companies that today's students can relate to and thus internalize the knowledge acquired. The new 6e prepares students with the foundation they need to understand how companies gain and sustain competitive advantage while developing skills to become successful leaders capable of making well-reasoned strategic decisions. As sole author, Rothaermel continues to provide an unmatched tight linkage between the concepts and cases, resulting in engaging and enjoyable content.